Helical Oxidovanadium(IV) Salen‐Type Complexes: Synthesis, Characterisation and Catalytic Behaviour. Issue 33 (25th September 2013) - Barman, Sanmitra; Patil, Smita; Desper, John; Aikens, Christine M.; Levy, Christopher J.
Abstract: Chiral [VO(salen)] complexes ( R, R )‐7 and ( R, R )‐8 were synthesised by ligand replacement from [VO(acac)2 ] with the resolved (1 R, 2 R )‐cyclohexyl ligands 3, 3′‐[(1 R, 2 R )‐1, 2‐cyclohexane‐diylbis(nitrilomethylidyne)]bis‐4‐phenanthrenol [( R, R )‐3 ] and 3, 3′‐[(1 R, 2 R )‐1, 2‐cyclohexanediylbis(nitrilomethylidyne)]bisbenz[ a ]anthracen‐1‐ol [( R, R )‐4 ], respectively. Similarly, complexes ( R )‐9 and ( R )‐10 were synthesised using the ( R )‐binaphthyl ligands 3, 3′‐[(1 R )‐(1, 1′‐binaphthalene)‐2, 2′‐diylbis(nitrilomethylidyne)]bis‐4‐phenanthrenol [( R )‐5 ] and 3, 3′‐[(1 R )‐(1, 1′‐binaphthalene)‐2, 2′‐diylbis(nitrilomethylidyne)]bis‐benz[ a ]anthracen‐1‐ol [( R )‐6 ], respectively. These complexes were characterised by IR spectroscopy, ESI‐TOF‐MS, electronic absorption spectroscopy and circular dichroism (CD). Single crystal X‐ray analysis of ( R, R )‐7 and ( R, R )‐8 revealed distorted square pyramidal geometries and a 1:1 ratio of diastereomeric M and P helical conformers. Solution CD studies in THF combined with DFT calculations indicate that the M conformer dominates in solution for ( R, R )‐7 . Preliminary catalytic oxidation of thioanisole with H2 O2 and 1 % [VO(salen)] showed good selectivity for sulfoxides over sulfones but low enantioselectivities (8 to 33 %) which are solvent dependent but insensitive to the catalyst used. Abstract : Chiral helical [VO(salen)] complexes have been synthesised, characterised and examined as catalysts for the asymmetric sulfoxidation of thioanisole with 30 % hydrogen peroxide.